Obowiązek świadczenia usług magazynowania paliw gazowych. Problematyka prawna - Będkowski-Kozioł, Michał (Kwartalnik Prawa Publicznego, 2013)
The benefits of gas storage include short- and long-term balancing of the gas system, further enhancement of the security of gas supply and, last but not least, optimization of gas system users’ behaviour through increased market liquidity. In this regard, Third Party Access (TPA) to Gas Storage Facilities plays in the opinion of EU Legislature an important step for the creation of well-functioning and competitive internal gas market within the EU. The legal basis for TPA to Storage Facilities are set out in Directive 2009/73/ EC as well as Regulation (EC) No. 715/2009. Relevant provision are implemented in Poland in Energy Law Act of 10th of April 1997, in Articles 4c and 4f-4i as well as Regulations of the Minister of Economic Affairs, in form of the general obligation of the relevant Storage System Operators (SSO) to provide storage services for interested system users. The main problem in legal determination of the obligations to provide storage services is, that storage facilities do not meet the criterion of an essential facility in the meaning of competition and energy regulatory law, i.e. the access to them is not indispensable to enter the gas market, however it helps the system users to adapt to market fluctuations more easily and thus benefit from the market liberalization. In this regard, a reasonable approach to TPA to Storage Facilities is required, both on the side of legislature as well as on the side of public bodies responsible for the enforcement of storage service obligation. In respect to the above mentioned problems TPA to Storage Facilities has not an absolute character under the energy law. In contrary, SSO has the right to refuse the storage services, if under special circumstances, reasons for legitimate refusal occur. The practical enforcement of TPA provisions in energy law depends on punctual and reasonable formulation of these reasons, as the access is a “rule”, whether the refusal an “exception”. The article analysis the scope of the TPA to storage facilities as well as legitimate reasons for refusal on a broad background of regulations, taking into account the newest amendment of Energy Law Act by the Act of 27th July 2013, aiming at further implementation of Directive 2009/73/EC into polish energy law system.